Enabling access to plant genetic resources for adaptation to climate change in 8 countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To support food security through the exchange and sustainable use of seeds, the United Nations negotiated the International Treaty on Plant Genetic Resources for Food and Agriculture (IT PGRFA). Bioversity International, IRRI, the CGIAR Genebank Platform and partners worked on promoting and enabling the implementation of the treaty in 8 developing countries.